STRATEGI KOMUNIKASI ISLAM DALAM PEMBENTUKAN KARAKTER INSAN KAMPUS (Studi Penerapan P3AI Bagi Mahasiswa UTU) - Muzakkir, Muzakkir (Universitas Teuku Umar, 2019)
The practice of effective communication is to change attitudes, change thinking, and change behavior both in speech and in action. The aim of the strategy in general is to determine and communicate a picture of vision and policy. The strategy describes the direction supported by various available resources. The communication strategy undertaken is macro and the process takes place vertically pyramid. In the context of science, Islamic communication has a main reference which is a way of life for Muslims, namely the Qur'an and the Hadith of the Prophet Muhammad. These two main sources provide characteristics of Islamic communication. In addition to the Qur'an and Hadith, the books delivered by the scholars and other disciplines also contributed to the development of communication science in general and Islamic communication in particular. Islam is a guide to life, which has provided various instructions in all areas of human communication. In fostering the character of students through the Development of Islamic Education Development Program (P3AI) more concerned with the final result (pragmatic) to get directly Islamic values.Keywords: Strategic, Islam Communcation, Character Building